Microgeração solar fotovoltaica conectada à rede: análise da qualidade da energia - Santiago, Gregory Luid Souza (Brasil, 2017)
Distributed photovoltaic systems currently have a great potential for growth, due to several factors that make it quite attractive, among them: tariff parity reached in the coming years in some countries, reduction of installation costs, government incentives, and sector regulation, among others. Since these are relatively new types of systems, many researches have been carried out to study the behavior of a distributed photovoltaic generation system connected to the distribution grid. In this sense, the main objective of this work is to analyze the impact generated in energy quality by the installation of a Grid-Connected Photovoltaic System (GCPV) installed in UFERSA, located in Mossoró/RN. Through the evaluation of the main parameters of energy quality generated by the GCPV, it was verified that the installation of a distributed photovoltaic system connected at low voltage causes small changes in some parameters, such as elevation in the steady state voltage, reduction of the power factor of the installation and increase in the value of the total harmonic distortion rate of current. In the work in question, all variations found did not exceed the limits established by the current regulations. It was also verified that the installation of the GCPV caused a daily reduction of up to 38% in the average active energy consumed, considering the phase in which the system is interconnected
Solar grid-connected photovoltaic microgeneration: energy quality analysis
Keywords: Geração distribuída; Energia solar fotovoltaica; Sistemas fotovoltaicos; Medição de energia elétrica; Distributed generation; Photovoltaic solar energy; Photovoltaic systems; Measurement of electrical energy; ENGENHARIAS::ENGENHARIA ELETRICA